Lead poisoning in opium-addicted subjects, its correlation with pyrimidine 5′-nucleotidase activity and liver function tests - Fakoor, Mandana; Akhgari, Maryam; Shafaroodi, Hamed (International journal of preventive medicine, 2019)
Background: Lead may be added to the opium by drug smugglers. It can cause elevated blood lead level (BLL) in opium-addicted patients. Erythrocyte pyrimidine 5′-nucleotidase (P5N) activity is susceptible to high BLL. The aim of this study was to find out whether opium-addicted patients show erythropathy and elevated liver enzymes explainable by high BLL and decreased P5N activity. Methods: Forty orally opium-addicted subjects and 40 normal healthy volunteers were enrolled in this study. BLL was measured in whole blood specimens using atomic absorption spectrometry instrumentation. Enzymatic activity, protein amount of P5N, and erythrocyte purine/pyrimidine ratio were determined. Blood films were analyzed for the presence of basophilic stippling of red cells and hemolytic anemia. The level of liver function enzymes was measured. Results: The mean BLL for opium-addicted patients was significantly higher than control group (P < 0.001). On the contrary, P5N activity showed a valid decrease in opium-addicted patients when compared with control group (P < 0.001). In line with repressed P5N activity, erythrocyte purine/pyrimidine ratio in patients was lower than control group (P < 0.001). A statistically significant reverse correlation was found between BLL and P5N activity (P < 0.05, r = −0.85). The prevalence of both basophilic stippling (P < 0.001, z = 6.62) and hemolytic anemia (P < 0.001, z = 6.52) in study population was significantly associated with elevated BLL. We could not find any significant correlation between serum level of liver enzymes and BLL. Conclusions: Opium-addicted patients in Tehran, Iran, are at high risk of lead poisoning which may result in hematologic problems and possibly hepatic damage.